Quantitative estimates of the variations of refractive index and gain with carrier density in GaAs/GaAIAs semiconductor injection lasers - Poh, B. S. (Institusi Jurutera Malaysia, 1984)
Quantitative estimates are made of the varia- tions of real refractive index (n ') and gain (g) with carrier density (N) in the GaAs/GaA1As d. h. laser with active-layer p-doping to 4 x 1017 cm-3 and operating at 297K. It is found that the value of Isn' should lie anywhere between -0.01 and -0.05, and the value of On 'faN should lie between -1.0 x 1(J20 cm~ . The value of a in the gain relation, g = a In(N), should lie between 100 cm-1 and 600 cm-1. A pro- portionality constant, A, is defined for the variation of }l with N, }l being the ratio of the real refractive index variation to the variation of the imaginary part of the complex refractive index. Graphs of A as a function of a are plotted, from which a value of a may be chosen together with the corresponding value of A.